Functional genomic approach to the study of biodiversitywithin Trichoderma - Monte E; Hermosa M R; Gonzalez F J; Rey M; Cardoza R E; Gutierrez S; Delgado Jarana J; Llobell A (浙江大学学报. 农业与生命科学版)
Trichoderma is a fungal genus of great and demonstrable biotechnological value, but its genome is poorly surveyed compared with other model microorganisms. Due to their ubiquity and rapid substrate colonization, Trichoderma species have been widely used as biocontrol organisms for agriculture, and their enzyme systems are widely used in industry. Therefore, there is a clear interest to explore beyond the phenotype to exploit the underlying genetic systems using functional genomics tools. The great diversity of species within the Trichoderma genus, the absence of optimized systems for its exploration, and the great variety of genes expressed under a wide range of ambient conditions are the main challenges to consider when starting a comprehensive functional genomics study. An initial project started by three Spanish groups has been extended into the project TRICHOEST, funded by the EU (FP5, QLRT-2001-02032) to target the transcriptome analysis of selected Trichoderma strains with biocontrol potential, in conditions related to antagonism, nutrient stress and plant interactions. Once specific conditions were defined, cDNA libraries were produced and used for EST sequencing. Nine strains from seven Trichoderma species have been considered in this study and an important amount of gene sequence data has been generated, analyzed and used to compare the gene expression in different strains.In parallel to sequencing, genomic expression studies were carried out by means of macro-arrays to identify genes expressed in specific conditions. In silico analysis of DNA sequencing data together with macro-array expression results have lead to a selection based on the potential use of the gene sequences. The selected clone sequences were completed and cloned in appropriate vectors to initiate functional analysis by means of expression studies in homologous and heterologous systems.